Evaluation Mangrove Density on the North Coast as a Means of Mitigation Danger Tidal Flood: Case Study of Demak Regency - Fikriyah, Inayatul; Dewa, Jhon Jhohan Putra Kumara (Jurnal Ilmiah Telsinas, 2025)
This study focuses on assessing the density of mangrove forests on the north coast of Demak Regency as an independent mitigation effort against tidal flooding. The impact of tidal flooding can be observed directly, such as damaged ponds and agricultural land, inundated road infrastructure, submerged houses, and disruption of livelihoods. This study is crucial because it provides data and spatial analysis to understand the current level of mangrove density, identify vulnerable areas and inform appropriate mitigation actions before the impact of tidal flooding. The study's novelty is that it focuses on specific density and vulnerability levels and uses significant short-term cover change analysis. Using spatial analysis methods through Geographic Information Systems (GIS) and satellite imagery from 2018-2023, several areas along the coast have mangrove densities varying from 1200-3400 trees per hectare. There was a 27.3% reduction in mangrove cover mainly due to changes in land use to ponds. Overlay analysis combining mangrove density with flood hazard maps and geographic information also maps how different mangrove areas are strongly related to tidal flooding. Areas with mangrove density <2000 trees per hectare are much more vulnerable to tidal flooding, which is worse at lower and better at higher ranges. The findings suggest that coastal engineering using soft hybrids, which integrate breakwater structures and mangrove rehabilitation, will be more effective in achieving long-term coastal resilience than using hard engineering techniques alone, support the integration of mangrove density thresholds into coastal infrastructure planning to enhance resilience against tidal flooding. As an effective policy for coastal management, a minimum standard of 3,000 mangrove trees per hectare is needed, and Demak Spatial Planning is needed to focus more on mangrove conservation within the Demak policy framework.